Intellectual Property Rights from an Islamic Legal Perspective - Hani Sholihah (al-Afkar, Journal For Islamic Studies, 2026)
Intellectual Property Rights (IPR) are a crucial issue in the modern world, as the economic and social value of ideas, innovations, and human intellectual works increases. In the context of Islamic law, the discussion of IPR presents a unique challenge because it is not found explicitly in classical Islamic jurisprudence literature. This article aims to explore the Islamic legal perspective on IPR through the approaches of maqasid al-shari'ah, qiyas, and contemporary ijtihad. This study analyzes various types of IPR, such as copyright, patents, and trademarks, within the framework of basic Islamic principles such as justice, ownership, and the prohibition of unjust appropriation of others' rights. In addition, this article examines the implementation practices of IPR law in modern Muslim countries and the responses of contemporary Islamic scholars to the protection of intellectual works. The results of the study indicate that although IPR is a concept born from modern Western law, its basic principles can be synergized with Islamic values, as long as they do not conflict with sharia principles. Therefore, strengthening IPR regulations within the framework of Islamic law is important as a form of protection of the moral and economic rights of creators, as well as a means of maintaining the public interest in Muslim society.